Multi-spinon and antiholon excitations probed by resonant inelastic x-ray scattering on doped one-dimensional antiferromagnets. (11th July 2018) - Kumar, Umesh; Nocera, Alberto; Dagotto, Elbio; Johnston, Steve
Abstract: Resonant inelastic x-ray scattering (RIXS) at the oxygen K -edge has recently accessed multi-spinon excitations in the one-dimensional antiferromagnet (1D-AFM) Sr2 CuO3, where four-spinon excitations are resolved separately from the two-spinon continuum. This technique, therefore, provides new opportunities to study fractionalized quasiparticle excitations in doped 1D-AFMs. To this end, we carried out exact diagonalization studies of the doped t – J model and provided predictions for oxygen K -edge RIXS experiments on doped 1D-AFMs. We show that the RIXS spectra are rich, containing distinct two- and four-spinon excitations, dispersive antiholon excitations, and combinations thereof. Our results highlight how RIXS complements inelastic neutron scattering experiments by accessing additional charge and spin components of fractionalized quasiparticles.